1990
DOI: 10.1016/0014-5793(90)81318-i
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphate‐hydrolysis ‐ a protective mechanism against alkaline stress?

Abstract: Different microorganisms, including yeast and algae, accumulate large amounts of polyphosphates. However, the physiological role of polyphosphates is largely unknown. In vivo a~ p NMR studies, carried out in the unicellular alga, Dunaliella salina, demonstrate that cytoplasmic alkalization induces massive hydrolysis of polyphosphates, which is correlated kinetically with the recovery of cytoplasmic pH. Analysis of acid extracts of the cells indicates that long-chain polyphosphates are hydrolysed mainly to trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…PolyP has also been suggested to function in the neutralization of microalgal cells that become alkalinized when incubated in high concentrations of ammonium (Pick et al, 1990). In Dunaliella salina, the addition of 20 mM ammonium increased the cytosolic pH and reduced cellular ATP levels.…”
Section: Polyp During Stationary Phase and Other Abiotic Stressesmentioning
confidence: 99%
“…PolyP has also been suggested to function in the neutralization of microalgal cells that become alkalinized when incubated in high concentrations of ammonium (Pick et al, 1990). In Dunaliella salina, the addition of 20 mM ammonium increased the cytosolic pH and reduced cellular ATP levels.…”
Section: Polyp During Stationary Phase and Other Abiotic Stressesmentioning
confidence: 99%
“…Remarkably, human mitochondrial NAD kinase has been recently identified to have the ability to utilize both ATP and polyP as the phosphoryl donor (Ohashi et al, 2012). Neglected and long regarded a molecular fossil, polyP has a variety of significant functions in bacteria such as a (i) source of energy (Kulaev, 1979; Wood and Clark, 1988; Kulaev et al, 1999b), (ii) phosphate reservoir (Kulaev et al, 1999b), (iii) donor for sugar and adenylate kinases (Bonting et al, 1991; Hsieh et al, 1993; Phillips et al, 1993), (iv) chelator for divalent cations (Van Veen et al, 1993), (v) buffer against alkaline stress (Pick et al, 1990), (vi) regulator of development (Gezelius et al, 1973), and (vii) structural element in competence for DNA entry and transformation (Reusch and Sadoff, 1988). Even though most of polyP research has been performed in microorganisms, the presence of polyP has been demonstrated in many mammalian tissues (Figure 4) such as rodent liver, kidney, lungs, brain, and heart (Kumble and Kornberg, 1995), rabbit heart (Seidlmayer et al, 2012a,b), as well as in human granulocytes (Cowling and Birnboim, 1994), platelets (Smith et al, 2006; Smith and Morrissey, 2008a; Morrissey et al, 2012), and fibroblasts (Pisoni and Lindley, 1992).…”
Section: What Is Inorganic Polyphosphate?mentioning
confidence: 99%
“…N is the limiting factor in P accumulation because N is required in protein synthesis, such as of ribosomal RNA, which incorporates P [ 33 , 42 ]. In the case of N limitation, uptake can still occur through a luxury uptake pathway where polyphosphates accumulate within C. vulgaris cells, which hydrolyse these to PO 4 -P [ 67 ]. This described effect of N limitation on P removal was observed in a study conducted by Li et al [ 26 ] using a mixture of Chlorella sp.…”
Section: Discussionmentioning
confidence: 99%